MRI biomarkers of proximal nerve injury in CIDP. Issue 1 (4th December 2017) - Lichtenstein, Thorsten; Sprenger, Alina; Weiss, Kilian; Slebocki, Karin; Cervantes, Barbara; Karampinos, Dimitrios; Maintz, David; Fink, Gereon R.; Henning, Tobias D.; Lehmann, Helmar C.
Abstract: Objective: To evaluate the utility of nerve diffusion tensor imaging (DTI), nerve cross‐sectional area, and muscle magnetic resonance imaging (MRI) multiecho Dixon for assessing proximal nerve injury in chronic inflammatory demyelinating polyneuropathy (CIDP). Methods: In this prospective observational cohort study, 11 patients with CIDP and 11 healthy controls underwent a multiparametric MRI protocol with DTI of the sciatic nerve and assessment of muscle proton‐density fat fraction of the biceps femoris and the quadriceps femoris muscles by multiecho Dixon MRI. Patients were longitudinally evaluated by MRI, clinical examination, and nerve conduction studies at baseline and after 6 months. Results: In sciatic nerves of CIDP patients, mean cross‐sectional area was significantly higher and fractional anisotropy value was significantly lower, compared to controls. In contrast, muscle proton‐density fat fraction was significantly higher in thigh muscles of patients with CIDP, compared to controls. MRI parameters showed high reproducibility at baseline and 6 months. Interpretation: Advanced MRI parameters demonstrate subclinical proximal nerve damage and intramuscular fat accumulation in CIDP. Data suggest DTI and multiecho Dixon MRI might be useful in estimating axonal damage and neurogenic muscle changes in CIDP.